2005
DOI: 10.1111/j.1067-1927.2005.00130311.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C prevents inflammation yet stimulates angiogenesis to promote cutaneous wound healing

Abstract: Activated protein C (APC) is a serine protease that plays a central role in physiological anticoagulation, and has more recently been shown to be a potent anti-inflammatory mediator. Using cultured human cells, we show here that APC up-regulates the angiogenic promoters matrix metalloproteinase-2 in skin fibroblasts and umbilical vein endothelial cells, vascular endothelial growth factor in keratinocytes and fibroblasts, and monocyte chemoattractant protein-1 in fibroblasts. In the chick embryo chorioallantoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 60 publications
6
109
3
Order By: Relevance
“…Activated protein C was initially identified as an anticoagulant; however, recent studies have revealed that it has important antiinflammatory properties (4). We have now shown that APC may be detrimental to articular cartilage through its promotion of the degradation of aggrecan and collagen by activating MMPs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Activated protein C was initially identified as an anticoagulant; however, recent studies have revealed that it has important antiinflammatory properties (4). We have now shown that APC may be detrimental to articular cartilage through its promotion of the degradation of aggrecan and collagen by activating MMPs.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to its anticoagulant role, APC has significant antiinflammatory properties, such as decreasing proinflammatory cytokine synthesis and reducing leukocyte recruitment (4). In vivo, APC protects against the lethal effects of endotoxemia in animal models and suppresses lipopolysaccharide-induced tumor necrosis factor ␣ (TNF␣) production (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have indicated that APC is either activating proteases that degrade the extracellular matrix [27,28] and/or activating receptor(s) that initiate signaling pathways to increase invasion and chemotaxis. Other studies have shown that the ability of APC to interact with EPCR and PAR-1 is a critical aspect of the mechanism responsible for altering inflammation, proliferation, and apoptosis [20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…APC increases proliferation and migration in keratinocytes by increasing the expression and activation of matrix metalloprotease-2 (MMP-2) [27]. Further, using a rat wound healing model, APC treatment reduced neutrophil infiltration and increased angiogenesis through MMP activation [28]. The initial studies looking at APC and cancer cell migration used ovarian cancer and choriocarcinoma cells in a transwell invasion assay [29].…”
Section: Introductionmentioning
confidence: 99%